Communication Strategy in Facing the Crisis of Regional Head Leadership in Indonesia - Fahirah, Raisah; Hazri, Baiq Marcelina Geovani; Yasmin, Adelina Putri; Harahap, M. Yasim; Fadly, Edward (AMK : Abdi Masyarakat UIKA, 2024)
This study aims to: 1) determine the impact of the crisis of leadership of regional heads in Indonesia and its resolution; 2) administrative techniques in managing correspondence emergencies in Indonesia. A literature review is a method used in this study. In the era of globalization, of course, every association or organization, private and government, certainly has long-term goals to achieve through planned activities. The data used in this study are secondary data, which come from articles, theses, books, leaflets, journals, e-books, and other sources that are still related to the problems in this study. This study used qualitative descriptive analysis as a data analysis method. Communication strategies in the leadership crisis in Indonesia are carried out by 1) Prioritizing religious principles; 2) being able to lead; 3) Developing further determination; 4) Improving education standards; 5) and legal remedies in Indonesia. An important component of crisis management is the implementation of crisis communication strategies for in-depth community communication and information filtering.